The Effect of public health expenditure on childhood mortality in Southern Africa (SADC) - Nyamuranga, Chamunorwa (KDI School, 2016)
This study sought to examine the effect of public health expenditure on childhood mortality in Southern Africa region. The empirical approach uses longitudinal data sourced from the World Development Indicators (World Bank) for the period 2000-2013. Infant and under-five mortality rates were used as indicators for childhood mortality. To diminish the possible confounding influence of public health expenditures in the child mortality regressions, we use an instrumental variable approach based on Dynamic Panel estimators or the General Method of Moment (GMM). The study finds that in Southern Africa region, public health expenditure has a strong impact on reducing both infant and under-five mortality rates. Moreover, the study finds that improvements in water sanitation and female literacy all work together to reduce the plausibility of infant and under-five deaths. These findings corroborate previous related empirical evidence for developing countries. Overall, from a policy standpoint, the empirical estimates call for public health policy makers in less-industrialized regions to pay close attention to three very basic measures. These include: improved water sanitation, female literacy along with increased public spending on health as these are all important factors that can help to decrease infant and under-five fatalities in Southern Africa.
Thesis(Master) --KDI School:Master of Development Policy,2016